Respostas
respondido por:
1
f[x] = 2x - 1 / x - 3
Trocando x por y e isolando y
y = 2x - 1 / x - 3
x = 2y - 1 / y - 3
Sobe multiplicando
x [ y - 3 ] = 2y - 1
xy - 3x = 2y - 1
xy - 2y = 3x - 1
Colocando y em evidência
y [ x - 2 ] = 3x - 1
y = 3x - 1 / x - 2
Trocando x por y e isolando y
y = 2x - 1 / x - 3
x = 2y - 1 / y - 3
Sobe multiplicando
x [ y - 3 ] = 2y - 1
xy - 3x = 2y - 1
xy - 2y = 3x - 1
Colocando y em evidência
y [ x - 2 ] = 3x - 1
y = 3x - 1 / x - 2
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás